DETERMINAN KEBERADAAN RISK MANAGEMENT COMMITTEE PADA PERUSAHAAN GO PUBLIC DI INDONESIA - Mona Ajeng Puspaningrum; Sugeng Pamudji (Diponegoro Journal of Accounting, 2013)
This study aims to examine the  information about The determinants of existence Risk Management Committee in Indonesia. This study was conducted by using independent variables are number Board of Commissioners, Proportion Independent Commissioner, Reputation of External Auditor, Corporate Complexity, Leverage and Financial Reporting Risk and its was used control variable is size of company. Existence of Risk Management Committee has two forms, they are Risk Management Committee joined with the Audit Committee and Risk Management Committee, which is separated from the Audit Committee or referred Separate Risk Management Committee (SRMC). This research was conducted using Logistic Regression as a test of the hypothesis. Data collection in this study using purposive sampling to non-banking financial companies listed at the Indonesia Stock Exchange in 2011. as many as 219 companies are used as samples in this study. Result of this study showed that the variables that affect existence of Risk Management Committee joined with the Audit Committee is affiliated with the Audit Committee is Reputation of External Auditor. Meanwhile, the variables that affect the existence of a separate Risk Management Committee separated from the Audit Committee is Leverage.